Microrheological properties and local structure of ι-carrageenan gels probed by using optical tweezers. (April 2023) - Geonzon, Lester C.; Kobayashi, Motoyoshi; Tassieri, Manlio; Bacabac, Rommel G.; Adachi, Yasuhisa; Matsukawa, Shingo
Abstract: Iota carrageenan (IC) is one of the most important gelling carrageenans in food and biotechnological applications; however, some of its potential applications have been constrained by its weak gelation ability. In order to better understand the origin of the weak mechanical response of IC gels, the hierarchical network structure based on meso- and microrheological properties of IC gels at 20 °C were probed via passive and active microrheology both performed by using optical tweezers (OT). Passive microrheology captures a wide spectral content of IC viscoelastic properties, revealing a rubbery plateau of the elastic modulus at relatively high frequencies for all IC concentrations; thus, uncovering the dynamics of the network. Moreover, different microstructures of IC gels were inferred by analyzing the concentration-dependent stress response when applying large deformation to the network. At low IC concentration, yielding was observed as indicated by the stress-independent response vs. strain, implying the structural rearrangement and disentanglement. As the IC concentration increased, the yielding diminished with increasing strain rate due to increased entanglement density, which limits the rearrangement of clusters. Therefore, this study presents novel insights into the meso- and microscale properties of IC gels that otherwise would not be accessible by conventional bulk rheology and submicroscopic probe diffusion measurements. Graphical abstract: Image 1 Highlights: Optical tweezers-based microrheology provides access to the mesoscopic properties of iota carrageenan (IC) gels. Passive microrheology captures a wide spectral content of IC viscoelastic properties uncovering the dynamics of the network. New insights into the hierarchical structure of IC gels were provided, especially at the mesoscopic scale.